PENGARUH DIGITAL MARKETING DALAM MENINGKATKAN PEMASARAN PADA UMKM DI DESA BUSUNG - Evita Sandra; Ahmad Yani; Surya Kusumah; Fatahuddin, Fatahuddin; Abdul Basyid (JURNAL PENGABDIAN MANDIRI, 2025)
This study aims to analyze the influence of digital marketing in improving the marketing of MSME products in Busung Village, Bintan. Busung Village has several superior products, such as gonggong crackers, which have the potential to be marketed more widely. This community service program is carried out through training and mentoring which includes branding strategies, use of social media, and marketplace management. The results of the activities show an increase in understanding and application of digital marketing by MSME players, which has an impact on increasing the number of orders and income. However, there are still challenges such as limited internet access and difficulties in creating consistent content. Therefore, further training and infrastructure support are needed to optimize the potential of digital marketing for MSMEs. With increased support, MSMEs in Busung Village have the potential to expand their market reach, improve their competitiveness, and contribute to local economic growth.